Multi‐modal combination therapy rescued a frequent ischemic stroke patient due to giant cell arteritis. Issue 3 (13th January 2019) - Takahashi, Yoshiaki; Sato, Kota; Matsumoto, Namiko; Kawahara, Yuko; Yunoki, Taijun; Shang, Jingwei; Takemoto, Mami; Hishikawa, Nozomi; Ohta, Yasuyuki; Yamashita, Toru; Abe, Koji
Abstract: Ischemic stroke (IS) due to giant cell arteritis (GCA) is rare, but highly mortal. Here, we report a 72‐year‐old man who showed frequent IS with GCA. Initial therapy with prednisolone increased the frequency of IS, which disappeared after continuous multi‐modal combination therapy with corticosteroids, immunosuppressive agents, antiplatelets, and statin. The present case was discharged with independent walk, suggesting that a multi‐modal combination therapy rescued the GCA patient from frequent IS.